Water Absorption and HEMA Release of Resin-Modified Glass-Ionomers - Beriat, Nilufer Celebi; Nalbant, Dilek (European Journal of Dentistry, 2009)
Objectives: The aim of this study was to evaluate the water absorption and the amount of hydroxyethyl metacrylate (HEMA) level released from various resin modified glass ionomer cements.Methods: Advance, Vitremer and Protec-Cem resin modified glass ionomer cements were used to evaluate the HEMA release. Ten specimens were fabricated from each cement in 10 × 1 mm height. Thirty specimens were immersed in glass containers filled with 20 ml deionized water. 1 ml solution was taken from the container at 10 minutes, 1 hour, 24 hour and 7 days intervals from each group and analyzed with high performance liquid chromatography (HPLC) machine and the results are presented in ppm. The data were subjected to Kruskal-Wallis, Mann-Whitney and Wilcoxon tests at a 0.05 significance level.Results: At all time intervals Vitremer showed highest HEMA release (10 min: 54.2 ppm; 1 h: 86.8 ppm; 24 h: 93.4 ppm) (P=0.0001). At the end of 10 minutes and first hour, following Vitremer, HEMA release was highest for Protec-Cem (10 min: 14.8 ppm; 1 h: 23.6 ppm) and then Advance (10 min: 5.5 ppm; 1 h: 18.8 ppm) (P<.05). Water absorption tests were performed according to the specifications of ISO 4049. Water absorption was highest for Vitremer and lowest for the Protec-Cem and the difference among cement groups was significant (P<.005).Conclusions: Vitremer showed the highest HEMA release and water absorption values and Protec-Cem showed the lowest values. HEMA release by time was significant for Advance cement. This release may be relevant both to the risk of adverse pulpal responses in patients and to the risk of allergy in patients and dental personnel. (Eur J Dent 2009;3:267-272)
Keywords: Water absorption; HEMA; Resin-modified glass-ionomers